Totally transaxillary endoscopic surgical release for congenital muscular torticollis - Sun, Junjie; Chen, Hao; Zhong, Zhihai; Xie, Qigen; Gao, Wenzong; Jiang, Hong; Yang, Yunjie; Gao, Pengfei (Frontiers in Surgery, 2025)
IntroductionThis study aims to present our experience with totally transaxillary endoscopic surgical release (TTESR) for the treatment of patients diagnosed with congenital muscular torticollis (CMT), as well as to compare the efficacy of this minimally invasive approach with that of conventional open surgical release (OSR).Materials and methodsA retrospective analysis was conducted on patients diagnosed with CMT who underwent either TTESR or OSR between January 2014 and December 2020. Herein, we provide a detailed description of the TTESR procedure. A total of 24 children were enrolled, with 6 patients undergoing TTESR and the remaining 18 undergoing OSR. The latter group was matched based on age and lesion location. Clinical data, including length of hospital stay, operative duration, intraoperative blood loss, and range of cervical rotation, were meticulously recorded. Comparative analysis was performed between the TTESR and OSR groups.ResultsIn our series, all 24 patients exhibited a marked improvement in cervical range of motion. No statistically significant differences were observed between the TTESR and OSR groups with respect to gender distribution, length of hospital stay, operative duration, or intraoperative blood loss. However, a significant difference was noted in the combined scores of scar evaluation and subjective assessments. No severe postoperative complications were reported. Additionally, with the accumulation of surgical experience, the average operative time for TTESR decreased to 40–50 min.ConclusionThis study demonstrates that TTESR serves an effective alternative to conventional OSR for correcting CMT, with the additional advantage of eliminating the aesthetically undesirable neck scar.